COMPARATIVE ANALYSIS OF EFFECTIVENESS AND ADVERS EFFECTS OF FESS AND CALDWELL-LUC PROCEDURE IN MAXILLARY CYST CASES: ARETROSPECTIVE STUDY - Das Sharodiya; Norjigitov Firdavs Nordirjonovich (World Scientific Research Journal, 2025)
Functional endoscopic sinus surgery (FESS) and Caldwell-Luc operation are both maxillary sinus cyst surgical procedures, and comparison between them regarding effectiveness and status of morbidity is still poorly documented. The retrospective cohort of 75 adults (60 patients underwent FESS and Caldwell-Luc operation was done in 15 patients) operated between 2017 and 2023 due to isolated maxillary sinus mucous retention cysts compared postoperative outcomes such as infraorbital nerve impairment (paresthesia or numbness) and pain (on Visual Analog Scale, VAS) facial edema, operation time, and hospitalization duration. Statistically (compared continuous variables by independent t-test and categorical variables by χ² or Fisher’s exact) analysis at an alpha level of p